Analiza i usprawnianie systemu zarządzania ryzykiem finansowym w przedsiębiorstwie - Michnik, Jerzy; Lo, Mei-Chen (Analysis and Improvement of Financial Risk Management in an Enterprise, 2007)
Rapid growth in financial markets, increasing volatility and globalization are the main reasons of growing importance of financial risk management (FRM) which nowadays becomes a serious matter not only for financial institution. Several risks, possible targets and measures of each dimension of risk, several types of tools and techniques come together to form the FRM. This is the reason why this is a complicated, multi-step and multi-dimensional process. In this paper we have proposed the hierarchical structure of the problem with the four aspects of FRM: measuring, monitoring, controlling and policy. The case study including questionnaires and discussions with Taiwanese electronic industry professionals was performed. The survey gave the opportunity to asses the relative importance (weight) of every element of the FRM system and how it works in the high technology manufacturing industry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 174-179